2015
DOI: 10.1021/acscatal.5b01090
|View full text |Cite
|
Sign up to set email alerts
|

Highly Robust Hydrogen Generation by Bioinspired Ir Complexes for Dehydrogenation of Formic Acid in Water: Experimental and Theoretical Mechanistic Investigations at Different pH

Abstract: Hydrogen generation from formic acid (FA), one of the most promising hydrogen storage materials, has attracted much attention due to the demand for the development of renewable energy carriers. Catalytic dehydrogenation of FA in an efficient and green manner remains challenging. Here, we report a series of bio-inspired Ir complexes for highly robust and selective hydrogen production from FA in aqueous solutions without organic solvents or additives. One of these complexes bearing an imidazoline moiety (complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
140
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 146 publications
(155 citation statements)
references
References 61 publications
12
140
2
1
Order By: Relevance
“…[31] This increase is presumed to be due to the high electron-donating effect of imidazole. [44] Although the nonmodified pyridine ring was low effective as a ligand moiety, its combination with an imidazoline ring which is a highly active ligand moiety improved catalytic activity and durability. [43] Additionally, although the catalytic activity of pyridyl-imidazoline complex (10) was lower than that of bisimidazoline complex 9 (Entry 10, TOF: 13 300 h −1 ), the improvement of the durability of FADH was observed.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…[31] This increase is presumed to be due to the high electron-donating effect of imidazole. [44] Although the nonmodified pyridine ring was low effective as a ligand moiety, its combination with an imidazoline ring which is a highly active ligand moiety improved catalytic activity and durability. [43] Additionally, although the catalytic activity of pyridyl-imidazoline complex (10) was lower than that of bisimidazoline complex 9 (Entry 10, TOF: 13 300 h −1 ), the improvement of the durability of FADH was observed.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…28-29,24-25, [30][31][32][33] For all these reasons significant efforts have recently been devoted to the development of new and more efficient transition metal complexes that can catalyze the hydrogenative reduction of CO2 with the objective of reaching high turnover numbers and high selectivity under milder conditions. 7 An additional challenge in this field is the discovery of catalysts sufficiently active to react with today's atmospheric CO2 concentrations, which are in the micromolar range, thereby potentially decreasing significantly its impact as a greenhouse gas.…”
Section: Introductionmentioning
confidence: 99%
“…[11,[15][16][17][18][19][20][21] We have found that catalysts in the family of half-sandwichC p* (1,2,3,4,5-pentamethylcyclopentadienyl) Ir complexes with N,Nbidentate ligands are effective for FA dehydrogenation in water withouta ny organic additives. [24,25] Additionally,L i's group has reported ac atalysth aving ab isimidazoline ligand. [23] Especially,n on-aromatic imidazoline ligands, in which the electrons delocalize within the amidine moieties, increase the electron density and lead to significantly enhanced catalytic activity.…”
mentioning
confidence: 99%